Segmentation-Based Classification of Plants Robust to Various Environmental Factors in South Korea with Self-Collected Database - Ganbayar Batchuluun; Seung Gu Kim; Jung Soo Kim; Kang Ryoung Park (Horticulturae)
Many plant image-based studies primarily use datasets featuring either a single plant, a plant with only one leaf, or images containing only plants and leaves without any background. However, in real-world scenarios, a substantial portion of acquired images consists of blurred plants or extensive backgrounds rather than high-resolution details of the target plants. In such cases, classification models struggle to identify relevant areas for classification, leading to insufficient information and reduced classification performance. Moreover, the presence of moisture, water droplets, dust, or partially damaged leaves further degrades classification accuracy. To address these challenges and enhance classification performance, this study introduces a plant image segmentation (Pl-ImS) model for segmentation and a plant image classification (Pl-ImC) model for classification. The proposed models were evaluated using a self-collected dataset of 21,760 plant images captured under real field conditions in South Korea, incorporating various environmental factors such as moisture, water droplets, dust, and partial leaf loss. The segmentation method achieved a dice score (DS) of 89.90% and an intersection over union (IoU) of 81.82%, while the classification method attained an F1-score of 95.97%, surpassing state-of-the-art methods.